Celastrol Loaded Nanoparticles With ROS-Response and ROS-Inducer for the Treatment of Ovarian Cancer - Niu, Weina; Wang, Jianguo; Wang, Qinyao; Shen, Jianjun (Frontiers in Chemistry, 2020)
Ovarian cancer is a gynecological cancer from which it is difficult to be completely cured. It is common to use regimens as an effective treatment for ovarian cancer, but these inevitably bring serious side effects. New treatment strategies and special drugs are needed to improve the prognosis of patients. Celastrol is a natural product, isolated from traditional medicine, that has been proven to be curative for inflammation and cancers. However, the non-targeting and low solubility of celastrol limit its clinical application. We prepared celastrol-loaded nanoparticles for the efficient treatment of ovarian cancer via oxidative stress amplification. In this work, a tumor-targeted, ROS-sensitive nanoparticle was designed, synthesized, and assembled into a drug delivery system that used celastrol. Folic acid (FA) groups on the surface of nanoparticles guide them to actively target the surface of the tumor cell membrane. Thioketal (TK) bonds in nanoparticles can be oxidized and broken into -SH within the ROS level of tumor tissues, which causes the breaking of the PEG hydrophilic shell layer of nanoparticles and promotes the release of celastrol. The released celastrol further stimulated the production of ROS and amplified the intracellular ROS level to promote the apoptosis of tumor cells, thus achieving a therapeutic effect on the celastrol treated ovarian cancer.